Stratification temperature affects the In Vitro germination of immature Prunus embryos - Daorden, Maria Elena (2004)
The rapid multiplication of clonal plants is desirable to shorten crossing programs in fruit tree breeding. In vitro stratification and germination allowed us to shorten the time and to improve the germination rates by embryo rescue. In this work, two stratification temperatures (0º and 4ºC) were compared and related to the development of interspecific hybrid embryos. The influence of embryo size was also determined, in order to optimise the process. Data showed that germination took place in 91% of the seeds when the stratification temperature was 4ºC. During stratification, embryo weight and embryo-weight increment were assessed at 30 and 60 days after sowing. Stratification temperature showed a significant effect in both embryo weight and embryo-weight increment 60 days after sowing, while embryo size showed a smaller influence. Embryo culture and stratification at 4 ºC allowed a satisfactory germination of immature seeds produced in crosses from breeding programs.